2016
DOI: 10.1097/htr.0000000000000193
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for Depression Posttraumatic Brain Injury: A Meta-analysis

Abstract: Pharmacotherapy after TBI may be associated with a reduction in depressive symptomatology. Given limitations within the available literature, further well-powered, placebo-controlled trials should be conducted to confirm the effectiveness of antidepressant therapy in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
0
25
2
Order By: Relevance
“…As far as we can determine, prophylactic pharmacological management to reduce the risk of depression post-TBI has not been considered in clinical guidelines for TBI. Prior systematic reviews and metaanalyses of the pharmacological management of symptomatic depression post-TBI report that pharmacotherapy post-TBI may be associated with a reduction in depressive symptoms; 23,31,32 no systematic reviews could be found that have identified and synthesized the evidence for prophylactic pharmacological management of depression post-TBI.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we can determine, prophylactic pharmacological management to reduce the risk of depression post-TBI has not been considered in clinical guidelines for TBI. Prior systematic reviews and metaanalyses of the pharmacological management of symptomatic depression post-TBI report that pharmacotherapy post-TBI may be associated with a reduction in depressive symptoms; 23,31,32 no systematic reviews could be found that have identified and synthesized the evidence for prophylactic pharmacological management of depression post-TBI.…”
Section: Introductionmentioning
confidence: 99%
“…We recognize that a systematic review of randomized placebo-controlled trials is the highest level of evidence, but caution clinicians against changing their practice on the basis of the Kreitzer et al [9] study. Clinicians who continue to prescribe will be compliant with practice guidelines [7, 8] and the best available evidence [6, 9, 10]. Selective serotonin reuptake inhibitors (e.g., sertraline or citalopram) are generally recommended as first-line [7, 18, 22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Prior meta-analyses have concluded that antidepressant medications are effective for depression in a variety of neurological disorders [5], including TBI [6]. Correspondingly, selective serotonin reuptake inhibitors are recommended as first-line treatment for depression in recently published expert consensus clinical practice guidelines for management of TBI [7, 8].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Small open-label and placebo-controlled trials have found sertraline, citalopram, milnacipran, and methylphenidate effective for post-TBI depression (66). In a meta-analysis of randomized controlled trials (67), methylphenidate was also found to be effective for attention deficits after mTBI.…”
Section: Treatmentsmentioning
confidence: 99%